Antioxidant activity and physicochemical characteristics of lulo fruit cultivated in Brazil - Jessica Cristina; Pierina Carraro, Bianca; Paulus, Cristiane; Khristinne Cordeiro, Noélle; Costa Braga, Gilberto (Scientia Agraria Paranaensis, 2022)
Underused crops have been expanding in the market due to their nutritional and antioxidant characteristics. Lulo, or naranjilla, can be considered an underused crop because it is grown on a small scale in Colombia and has high nutritional value. The edaphoclimatic conditions of cultivation of this fruit can influence its post-harvest characteristics. Thus, the objective of the work was to evaluate the antioxidant activity and the physicochemical characteristics of lulo fruit obtained from cultivation in Brazil. The post-harvest variables analyzed were antioxidant activity by ABTS, DPPH, FRAP methods, phenolic compounds, flavonoids, lycopene, β-carotene, ascorbic acid, and physicochemical characteristics of acidity, soluble solids, and ratio. Twenty replicates were used for each variable, including three replicates for antioxidant analyses and two replicates for carotenoids; each replicate consisted of one fruit. The mean and standard deviation were calculated. The FRAP antioxidant activity method showed 81.40 mg Ferrous Sulfate g-1 (dry mass), ABTS 57.00 mg Trolox g-1 (dry mass) and DPPH 14.40 mg Trolox g-1 (dry mass). The flavonoids contents were 1.00 mg Quercetin g-1 (dry mass), which is considered low. Lulo fruit showed to be a good source of β-carotene (7.00 mg 100 g-1), lycopene (3.57 mg 100 g-1) and ascorbic acid (57.71 mg 100 g-1). The fruit is acidic (2.29 g Citric Acid 100 mL‑1), with low soluble solids content (5.12%) and low ratio (2.25).